1995
DOI: 10.1111/j.1600-0781.1995.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sunburn cells after exposure to ultraviolet light

Abstract: Sunburn cells (SBCs) appear in the epidermis shortly after acute UV damage, especially after exposure to UVB light. As yet, the mode of their formation remains to be satisfactorily elucidated. In order to characterize these cells, the expression of various markers of epidermal differentiation following UV exposure was investigated using immunhistochemical procedures. These were applied to paraffin-embedded (microwave technique) and frozen specimens of human skin 24 h after irradiation with 4 times the minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 20 publications
9
61
0
Order By: Relevance
“…It has been described that apoptotic cells (located in first suprabasal layers of the epidermis) do not develop beyond a ''basal-like'' differentiation pattern and also retain K5 (18). However, the arrested cells in Xpc…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that apoptotic cells (located in first suprabasal layers of the epidermis) do not develop beyond a ''basal-like'' differentiation pattern and also retain K5 (18). However, the arrested cells in Xpc…”
Section: Discussionmentioning
confidence: 99%
“…UV-induced sunburn cells (defined by pyknotic nuclei and eosinophilic cytoplasm) stain negatively for Dsgs and Dps (Bayerl et al 1995) and reduced desmosome molecule transcripts are frequently observed in UV-exposed keratinocytes (Li et al 2001;Murakami et al 2001;Sesto et al 2002;Rundhaug et al 2005). UVC (below 290 nm wavelength) results in caspase-dependent cleavage of Dsg1 and redistribution of Dsg1 from cell borders into the cytoplasm (Dusek et al 2006).…”
Section: Desmosomes and The Epidermal Barriermentioning
confidence: 99%
“…Keratins K6, K16, and/or K17, which are not usually expressed in the innate state of normal epidermis, have been reported to initially induce in the suprabasal layers as early as 6 hours after injury or during the first 24 to 48 hours of UVB irradiation. 48,[77][78][79][80][81] The increase of these epidermal keratins has a direct impact on epidermal cytoarchitectural alteration and its migratory behavior during re-epithelization. The presence of these keratins has been documented in early hair germs and in the companion layer of the outer root sheath during embryonic development and the mature hair follicle anagen.…”
Section: Discussionmentioning
confidence: 99%